(x-7)mũ 2=49
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(x^2+5\right)\left(x^2-49\right)=0\)
\(\left(x^2-49\right)=0\) vì \(x^2+5>0\)
\(\Rightarrow x^2=49\)
\(\Rightarrow x=\pm7\)
vậy \(x=\pm7\)
\(\left(x^2+5\right)\left(x^2-7\right)< 0\)
\(\left(x^2-7\right)< 0\)
\(\left(x-\sqrt{7}\right)\left(x+\sqrt{7}\right)< 0\)
\(\hept{\begin{cases}x-\sqrt{7}>0\\x+\sqrt{7}< 0\end{cases}}\) hoặc \(\hept{\begin{cases}x-\sqrt{7}< 0\\x+\sqrt{7}>0\end{cases}}\)
\(\hept{\begin{cases}x>\sqrt{7}\\x< -\sqrt{7}\end{cases}}\) hoặc \(\hept{\begin{cases}x< \sqrt{7}\\x>-\sqrt{7}\end{cases}}\)
đến đây tự làm tiếp
\(\left(x^2+5\right)\times\left(x^2-49\right)=0\)
Vậy \(\orbr{\begin{cases}x^2+5=0\\x^2-49=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x^2=-5\\x^2=49\end{cases}}\)
Mà \(x^2\ge0\Rightarrow x^2=-5\)(loại)
Vậy \(x^2=49\)
Nên \(\orbr{\begin{cases}x=7\\x=-7\end{cases}}\)
\(7^x\times49=7^{32}\)
\(\Rightarrow7^x\times7^2=7^{32}\)
\(\Rightarrow7^{x+2}=7^{32}\)
\(\Rightarrow x=30\)
7A=7^2+7^3+7^4+....+7^100
A=7+7^2+7^3+....+7^99
6A=7^100-7
khi đó ta có
a;2 mu x =2 mu 6 .Vậy x=6
e, 2x.4 = 128
<=> 2x . 22 = 27
=> x + 2 = 7
<=> x = 5
Vậy x = 5
f , ( x - 5)4 = (x - 5)6
<=> ( x - 5)4 - (x - 5)6 =0
<=> (x - 5)4. [1 - (x - 5)2] = 0
<=> (x - 5)4 (1 - x + 5)(1 + x - 5) = 0
<=> (x - 5)4 (6 - x)(x - 4) = 0
<=> \(\left[{}\begin{matrix}x-5=0\\6-x=0\\x-4=0\end{matrix}\right.\) <=> \(\left[{}\begin{matrix}x=5\\x=6\\x=4\end{matrix}\right.\)
Vậy x ={5; 6; 4}
49 . 7x = 2041
<=> 72. 7x = 74
=> 2 + x = 4
<=> x = 2
Vậy x = 2